THE EFFECT OF STANDARD OPERATIONAL PROCEDURES (SOP) AND COMPETENCY OF HEALTH PERSONNEL ON THE TIME OF MEDICAL RECORDING DOCUMENTS COMPLETION AT ASSALAM RSU, GEMOLONG - Dewi Arini, Liss Dyah; Istiqomah, Lailatul; Fanny, Nabilatul (Lux Mensana: Journal of Scientific Health, 2022)
At RSU Assalam Gemolong, the implementation of the SOP has not been fully implemented by health workers. General objective of this study was to determine the effect of SOP and health workers competence on completing time of inpatient medical record documents at RSU Assalam Gemolong. This type of research is quantitative analytic, cross sectional approach. The population is 115 respondents, the sample is 30 respondents, the sampling technique is purposive sampling. Data collection techniques using interviews and questionnaires. Data processing by collecting, editing, classifying, tabulating, presenting data. The results of the SOP analysis of the completeness medical record documents for inpatient medical record documents sometimes returned to medical record installation more than 2x24 hours. The health workers characteristic based on respondents’ group are 5 doctors (17%), 16 nurses (53%) and 9 medical records officers (30%). Characteristics of male 10 respondents (33%), female 20 respondents (67%). The result is 0.035 < 0.05, then there is an influence between SPO on the time of completeness of medical record documents. The result is 0.975 > 0.05, therefore there is no influence between the health workers competence on completing time medical record documents at RSU Assalam Gemolong. The conclusion of this research is that there is an influence between SPO on completing time of medical record documents and there is no effect of the health workers competence on completing time of medical record documents.